Private sector investment in infrastructure Project finance, PPP projects and PPP frameworks - Delmon, Jeff (Kluwer Law International, 2021)
Private Sector Investment in Infrastructure', now in its fourth edition, is a practical, hands-on book elucidating how the private sector (through ? Public-Private Partnerships (PPPs)) can furnish more efficient procurement, cheaper, faster, and better quality; refocus infrastructure services on service delivery, consumer satisfaction and life-cycle maintenance; and provide new sources of innovation, technological advances and investment, including through limited recourse debt (i.e., project financing).00PPPs are part of a fundamental, global shift in the role of the government ? from being the direct provider of public services to becoming the planner, facilitator, contract manager and/or regulator who ensures that local services are available, reliable, meet essential quality standards, and are affordable for users and the economy.00The past five years have posed some new severe challenges, a global pandemic, debt crises, and a global economic crisis. While the responses to these challenges are complex, the fundamentals remain unchanged. Infrastructure supports economic growth, creates jobs and improves livelihoods. Private investment in infrastructure is critical now more than ever, in the face of stiff competition from alternative uses of public funds.